Análisis comparativo en el control de los asistentes de voz Alexa y Google home como un sistema eficiente de búsqueda - Campoverde Morales, Miguel Ronny (2021)
In this Case Study, an attempt is made to broadly demonstrate a comparative analysis of the Alexa and Google Home voice assistants. society and lives in an experienced way every day, this novel system of proposing very fast answers has been in the market for some years now to try to understand or know through an efficient search, to be able to investigate, speak, know, treat, look and verify each Detail of this is very necessary and interesting, the proposals that we can receive for the searches we need. It is evident that these speakers or virtual voice assistants are going to completely renovate homes, in something that was only thought and seen in movies, using the voice, now it is possible and real today, assuming task solutions complex and immediate and fast answers in a matter of seconds, without the need to make an effort and this was born so that each person makes life easier. It also greatly simplifies the complexity of looking for some information, it also has many functions and models in which it can be achieved according to the needs and adaptation of prices for the user. According to what is discussed in this case study, the very necessary and important aspects of each one of them are deepened, in which it was investigative, explanatory, referring to the information provided about the environment and trying to emphasize in order to be clear about the necessary points and important in knowing every detail of the subject.